Network on a chip modeling wireless networks with asynchronous VLSI. - Manohar, R. (IEEE Communications magazine)
We introduce the notion of a network on a chip: a programmable asynchronous VLSI architecture for fast and efficient simulation of wireless networks. The approach is inspired by the remarkable similarity between networks and asynchronous VLSI. Our approach results in simulators that can evaluate network scenarios much faster than real time, enabling a new class of network protocols that can dynamically change their behavior based on feedback from in situ simulation. We describe our simulation architecture, and present results that validate our approach